The implementation of polycaprolactone (PCL) as an eco-friendly material in toy design development - Jameel Mohamed Kamil, Muhammad; Aliya Shaukat, Sarah (Journal of Graphic Engineering and Design, 2023)
Due to a substantial impact of hazardous materials in toy design, numerous toy companies have opted for an eco-friendly toy by promoting a legacy of innovation rather than waste and degradation. Furthermore, one of the most significant polymers for being recognised as a safe toy material is Polycaprolactone (PCL). However, in Malaysia, the study of Malaysian parent’s level of awareness in buying eco-friendly toys, their behaviour in purchasing and managing toys at home, as well as the preferences of play type for their children, is not widely discussed. Thus, forty (40) Malaysian parents have participated in an online survey conducted by the research team. The result of the study found that most Malaysian parents has a low level of awareness in buying eco-friendly toys for their children, lack the skills needed in handling broken or unused toys, and have selected criteria to be considered when purchasing a toy. Furthermore, a set of semiworking toy design was successfully developed using PCL as a proposal for potential future development and production. It is hoped that the outcome of this study will contribute to inspire future toy designers to account for Malaysian parent’s preferences when developing eco-friendly toys. Article history: Received (June 28, 2022); Revised (December 16, 2022); Accepted (January 4, 2023); Published online (March 1, 2023)